Optimalisasi Pengelolaan Sampah: Analisis Bank Sampah Resik Kutho Di Kota Surakarta - Buana, Pratama Angga (Universitas Multi Data Palembang, 2024)
Waste management poses a significant challenge in many regions, including Indonesia. This study aims to analyze and evaluate the performance of Resik Kutho Waste Bank in Surakarta City, focusing on effective and sustainable waste management strategies. A qualitative research method was employed, combining SWOT analysis and primary data from observations, interviews, and questionnaires distributed to waste bank managers and customers. The results show that Resik Kutho Waste Bank has internal strengths that can be leveraged for the development of more efficient waste management strategies, particularly in seizing existing opportunities. However, certain aspects such as financing and operational techniques need improvement. This study provides valuable insights for waste management at the community level, emphasizing the importance of integrating the waste bank's internal strengths with existing opportunities to achieve more sustainable waste management. Keywords— Waste Bank, Qualitative, Resik Kutho, Likert Scale, SWOT